Data Analytics Effective Methods for Presenting Results. - Samaddar, Subhashish; Nargundkar, Satish (Milton : Auerbach Publications, 2019)
If you are a manager who receives the results of any data analyst's work to help with your decision-making, this book is for you. Anyone playing a role in the field of analytics can benefit from this book as well. In the two decades the editors of this book spent teaching and consulting in the field of analytics, they noticed a critical shortcoming in the communication abilities of many analytics professionals. Specifically, analysts have difficulty in articulating in business terms what their analyses showed and what actionable recommendations were made. When analysts made presentations, they tended to lapse into the technicalities of mathematical procedures, rather than focusing on the strategic and tactical impact and meaning of their work. As analytics has become more mainstream and widespread in organizations, this problem has grown more acute. Data Analytics: Effective Methods for Presenting Results tackles this issue. The editors have used their experience as presenters and audience members who have become lost during presentation. Over the years, they experimented with different ways of presenting analytics work to make a more compelling case to top managers. They have discovered tried and true methods for improving presentations, which they share. The book also presents insights from other analysts and managers who share their own experiences. It is truly a collection of experiences and insight from academics and professionals involved with analytics. The book is not a primer on how to draw the most beautiful charts and graphs or about how to perform any specific kind of analysis. Rather, it shares the experiences of professionals in various industries about how they present their analytics results effectively. They tell their stories on how to win over audiences. The book spans multiple functional areas within a business, and in some cases, it discusses how to adapt presentations to the needs of audiences at different levels of management.
The Problem with Analysts: Black Swans, ML, and the FutureCHAPTER 11 "AS YOU CAN SEE ..."; Epilogue; INDEX
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Business -- Data processing; Business requirements analysis; Business analysts; COMPUTERS / Computer Graphics / General; COMPUTERS / Database Management / Data Mining; MATHEMATICS / Probability & Statistics / General